A Versatile Hybrid Mock Circulation for Hydraulic Investigations of Active and Passive Cardiovascular Implants. Issue 5 (July 2019) - Petrou, Anastasios; Granegger, Marcus; Meboldt, Mirko; Schmid Daners, Marianne
Abstract : During the development process of active or passive cardiovascular implants, such as ventricular assist devices or vascular grafts, extensive in-vitro testing is required. The aim of the study was to develop a versatile hybrid mock circulation (HMC) which can support the development of such implants that have a complex interaction with the circulation. The HMC operates based on the hardware-in-the-loop concept with a hydraulic interface of four pressure-controlled reservoirs allowing the interaction of the implant with a numerical model of the cardiovascular system. Three different conditions were investigated to highlight the versatility and the efficacy of the HMC during the development of such implants: 1) biventricular assist device (BiVAD) support with progressive aortic valve insufficiency, 2) total artificial heart (TAH) support with increasing pulmonary vascular resistance, and 3) flow distribution in a total cavopulmonary connection (TCPC) in a Fontan circulation during exercise. Realistic pathophysiologic waveforms were generated with the HMC and all hemodynamic conditions were simulated just by adapting the software. The results of the experiments indicated the potential of physiologic control during BiVAD or TAH support to prevent suction or congestion events, which may occur during constant-speed operation. The TCPC geometry influenced the flow distribution between the right and the left pulmonary artery, which was 10% higher in the latter and led to higher pressures. Together with rapid prototyping methods, the HMC may enhance the design of implants to achieve better hemodynamics. Validation of the models with clinical recordings is suggested for increasing the reliability of the HMC. Abstract : Supplemental Digital Content is available in the text.